Intravitreal Dexamethasone Implant (Ozurdex) for Ocular Toxocariasis - Yongwei Zhou; Fangyuan Zhen; Jiahui Wu; Shasha Wang; Xiaoyan Lu; Ge Yang; Zhirou Hu; Fei Chen; Qiuming Li; Shuqian Dong (Journal of Ophthalmology)
This study aimed to evaluate the efficacy and safety of intravitreal dexamethasone implants in the treatment of ocular toxocariasis (OT). A retrospective analysis was performed on 6 cases in which laboratory tests diagnosed OT. All patients were administered with intravitreal dexamethasone implants with or without vitrectomy. The average follow-up time was 19.7 months. All operated eyes achieved anatomic success, and all patients’ visual acuity was improved. Five of these six had a visual acuity of 20/100, and three had final acuity of 20/40 or even better. Intravitreal dexamethasone implants can be used to treat different types of OT, which not only effectively control inflammation and improve the patient’s vision but also reduce the use of systemic glucocorticoids.